Endorectal ultrasound and magnetic resonance imaging for staging of early rectal cancers: how well does it work in practice?. (1st April 2019) - Oien, Kristian; Forsmo, Håvard Mjørud; Rösler, Cornelia; Nylund, Kim; Waage, Jo Erling; Pfeffer, Frank
Abstract: Background: Rectal tumor treatment strategies are individually tailored based on tumor stage, and yield different rates of posttreatment morbidity, mortality, and local recurrence. Therefore, the accuracy of pretreatment staging is highly important. Here we investigated the accuracy of staging by magnetic resonance imaging (MRI) and endorectal ultrasound (ERUS) in a clinical setting. Material and methods: A total of 500 patients were examined at the rectal cancer outpatient clinic at Haukeland University Hospital between October 2014 and January 2018. This study included only cases in which the resection specimen had a histopathological staging of adenoma or early rectal cancer (pT1–pT2). Patients with previous pelvic surgery or preoperative radiotherapy were excluded. The 145 analyzed patients were preoperatively examined via biopsy ( n  = 132), digital rectal examination ( n  = 77), rigid rectoscopy ( n  = 127), ERUS ( n  = 104), real-time elastography ( n  = 96), and MRI ( n  = 84). Results: ERUS distinguished between adenomas and early rectal cancer with 88% accuracy (95% CI: 0.68–0.96), while MRI achieved 75% accuracy (95% CI: 0.54–0.88). ERUS tended to overstage T1 tumors as T2–T3 (16/24). MRI overstaged most adenomas to T1–T2 tumors (18/22). Neither ERUS nor MRI distinguished between T1 and T2 tumors. Conclusions: In a clinical setting, ERUS differentiated between benign and malignant tumors with high accuracy. The present findings support previous reports that ERUS and MRI have low accuracy for T-staging of early rectal cancer. We recommend that MRI be routinely combined with ERUS for the clinical examination of rectal tumors, since MRI consistently overstaged adenomas as cancer. In adenomas, MRI had no additional benefit for preoperative staging.